THE CULTURAL HERITAGE IN IMPLEMENTATION OF THE FOLK CRAFT TO THE PROCESS OF EDUCATION - KOŽUCHOVÁ, Mária; UHRINOVÁ, Miroslava (Trends in education, 2014)
The Slovak Republic ratified the Convention for the Safeguarding of the Intangible Cultural Heritage In 2006. School plays an irreplaceable role in recognition and protection of cultural, spiritual and historical values. We examined how teachers are prepared for this fact. We were interested in the self-evaluation attitude of teachers to implementation aspects of folk culture with regards to the traditional folk craft, as well as the practical application of the acquisition of folk craft in the educational process from the perspective of students. In our paper we present partial results of the research which was focused on the implementation of elements of folk culture into the educational process.
Keywords: regional education; traditional folk crafts; cultural traditions.